Tumor Molecular Imaging with Nanoparticles. (March 2016) - Cheng, Zhen; Yan, Xuefeng; Sun, Xilin; Shen, Baozhong; Gambhir, Sanjiv Sam
Abstract : ABSTRACT: Molecular imaging (MI) can provide not only structural images using traditional imaging techniques but also functional and molecular information using many newly emerging imaging techniques. Over the past decade, the utilization of nanotechnology in MI has exhibited many significant advantages and provided new opportunities for the imaging of living subjects. It is expected that multimodality nanoparticles (NPs) can lead to precise assessment of tumor biology and the tumor microenvironment. This review addresses topics related to engineered NPs and summarizes the recent applications of these nanoconstructs in cancer optical imaging, ultrasound, photoacoustic imaging, magnetic resonance imaging (MRI), and radionuclide imaging. Key challenges involved in the translation of NPs to the clinic are discussed.